Analysing the role of medulloblastoma exosomes as biomarkers and their functional contribution to metastasis - Jackson, Hannah K. (2021)
Introduction: Recurrent/metastatic medulloblastoma is a devastating disease with an abysmal prognosis of less than 10% five-year survival. Whilst primary tumours can be classified based on epigenetic and transcriptomic features, there is very little information regarding molecular signatures of metastatic tumours. The secretion of extracellular vesicles (EVs) has emerged as a pivotal mediator for communication in the tumour microenvironment during metastasis. The most investigated EVs are exosomes, nanovesicles secreted by all cell types and able to cross the blood-brain-barrier. The role of exosomes as vehicles for cell-to-cell communication between a tumour and its microenvironment is a relatively new concept, with only limited study of this potential mechanism in medulloblastoma. This study aims to gain insight into the differences between exosomes of primary and metastatic medulloblastoma cell lines to better understand how exosomal cargo may account for differences seen between these phenotypes and to identify their applicability as a prognostic biomarker of increased metastatic potential.